2019
DOI: 10.3389/fevo.2019.00214
|View full text |Cite
|
Sign up to set email alerts
|

Individual Spatial Consistency and Dietary Flexibility in the Migratory Behavior of Northern Gannets Wintering in the Northeast Atlantic

Abstract: non-breeding period. Our results indicate that a consistent migratory strategy can be effective regardless of wintering region or diet, but that there may be benefits to those individuals able to display flexibility. This appears to be an important behavioral strategy that may enhance individual condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 93 publications
1
16
0
Order By: Relevance
“…Actually, ‘Least Concern’ species are largely affected by threats at a global level (Dias et al 2019). The Portuguese shelf waters represent an important area for at least some Northern Gannet populations during their migratory and wintering periods (Kubetzki et al 2009, Grecian et al 2019). More information is needed to investigate the effects of bycatch on the demographic parameters of those populations, namely on recruitment of new breeders, since our data strongly suggest that immatures are more susceptible to bycatch than adult birds.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, ‘Least Concern’ species are largely affected by threats at a global level (Dias et al 2019). The Portuguese shelf waters represent an important area for at least some Northern Gannet populations during their migratory and wintering periods (Kubetzki et al 2009, Grecian et al 2019). More information is needed to investigate the effects of bycatch on the demographic parameters of those populations, namely on recruitment of new breeders, since our data strongly suggest that immatures are more susceptible to bycatch than adult birds.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that gouramis display repeatable inter-individual differences in latency to shoot, with related consequences on shooting performance and success. This is increasingly expected as such inter-individual differences in behaviour can play an important role in the ecology and evolution of foraging behaviours across species (Dall et al, 2012;Toscano et al, 2016;Metcalfe et al, 2016;Troxell-Smith and Mella, 2017;Snijders et al, 2018;Grecian et al, 2019;Hansen et al, 2020). Such repeatable inter-individual differences in latency to shoot have been observed in archerfish, (Jones et al, 2018) with analogous differences in latency to attack in other predatory fish (Szopa-Comley et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…among sexes [60], ages and individuals in migratory behaviour [61]. Recently, GLS loggers were used to study migration strategies of gannets nesting in the Northeast Atlantic [10,23,24,26,60] and Northwest Atlantic [25]. These loggers also made it possible to track long-term migration to assess marine pollution impact (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…banding and observations of birds at sea [46], that individuals vary in migration distance, spanning the area from the northern part of the American Atlantic coast to the Gulf of Mexico, but with no resident individuals in the Gulf of St. Lawrence, where waters are generally covered with ice during the winter. Across the breeding range of the species, migration strategies and non-breeding destinations are highly repeatable over consecutive years [10,25,26], and the net cost-benefit appears to be similar for all wintering areas in terms of energetics [10].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation